2015
DOI: 10.1007/s11892-015-0624-3
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Exposure to Substance Abuse and Risk of Type 2 Diabetes in Adulthood

Abstract: Type 2 diabetes (T2D) is a chronic non-communicable disease that is driven by insulin resistance as a result of increasing obesity and decreasing activity levels that occur with increasing age. This disease generally develops after the age of 40, but it is now increasingly diagnosed in children and young adults. Increasing evidence, however, suggests that T2D can originate during early development. It has been repeatedly found that malnutrition during the gestational period can result in intrauterine growth re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Seasonality of birth has been demonstrated for many aspects of metabolic syndrome, including high systolic blood pressure [82], obesity [83,84] and also dyslipidaemia, insulin resistance and CVD [85]. The seasonal pattern of birth for childhood autoimmune (type 1) diabetic patients was reported repeatedly (see, e.g., [96]), while the seasonality of birth for T2D adult persons was observed only in a few studies.…”
Section: Seasonality Of Birthmentioning
confidence: 99%
“…Seasonality of birth has been demonstrated for many aspects of metabolic syndrome, including high systolic blood pressure [82], obesity [83,84] and also dyslipidaemia, insulin resistance and CVD [85]. The seasonal pattern of birth for childhood autoimmune (type 1) diabetic patients was reported repeatedly (see, e.g., [96]), while the seasonality of birth for T2D adult persons was observed only in a few studies.…”
Section: Seasonality Of Birthmentioning
confidence: 99%
“…Similar to the human Dutch Hunger Winter famine case during World War II, environmental exposure to factors including nutritional, psychological, and social stress, toxins and substance abuse in early life may serve as triggers for epigenetic programming for various comorbidities later (Vaiserman, 2015a;Vaiserman, 2015b). In mammals, the epigenome may be subject to major epigenetic modifications during gametogenesis and early embryogenesis (Messerschmidt et al, 2014;Vaiserman, 2015a;Vaiserman, 2015b). In the early embryo, methylation levels are minimal to allow removal of gamete-specific methylation inherited from parents for the purpose of pluripotency.…”
Section: B Epigenetics and Human Diseasesmentioning
confidence: 99%
“…Demethylation process is considered near complete in primordial germ cells, whereas methylation of imprinted regions is protected in early embryos, thus allowing expression of specific parent-of-origin genes in early embryos (Messerschmidt et al, 2014). Therefore, epigenetic modifications elicited by environmental influences during these critical periods pertain across the life course, possibly resulting in unfavorable consequences in adulthood (Messerschmidt et al, 2014;Vaiserman, 2015a;Vaiserman, 2015b).…”
Section: B Epigenetics and Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such concerns are highly relevant, as there might be a genetic susceptibility to passing RA or other autoimmune diseases on to the offspring. Furthermore, it has been repeatedly found that fetal programming during the gestational period can result in intrauterine growth restriction and low birthweight, which can subsequently lead to the development of chronic diseases in adulthood . Early adverse fetal life exposures, such as maternal chronic disease, might thus program not only adverse birth outcomes but also have a lifelong impact on the health status of the exposed children .…”
Section: Introductionmentioning
confidence: 99%